Duration of HIV-1 Viral Suppression on Cessation of Antiretroviral Therapy in Primary Infection Correlates with Time on Therapy - Stöhr, Wolfgang; Fidler, Sarah; McClure, Myra; Weber, Jonathan; Cooper, David; Ramjee, Gita; Kaleebu, Pontiano; Tambussi, Giuseppe; Schechter, Mauro; Babiker, Abdel; Phillips, Rodney E.; Porter, Kholoud; et al. (PLoS ONE, 2013)
A minority of HIV-1 positive individuals treated with antiretroviral therapy (ART) in primary HIV-1 infection (PHI) maintain viral suppression on stopping. Whether this is related to ART duration has not been explored. Design: And Methods: Using SPARTAC trial data from individuals recruited within 6 months of seroconversion, we present an observational analysis investigating whether duration of ART was associated with post-treatment viraemic control. Kaplan-Meier estimates, logistic regression and Cox models were used. 165 participants reached plasma viral loads (VL) 12 weeks compared to ≤12 weeks (p=0.061). Cumulative probabilities of remaining 12 weeks. In multivariable regression, ART for >12 weeks was independently associated with a lower probability of being ≥400 copies/ml within 12 weeks of ART stop (OR=0.11 (95%CI=0.03,0.34), p
Keywords: HIV-1 Viral Suppression; Antiretroviral Therapy; Primary Infection